The role of Entrepreneurial Education in building student independence at MTs Hidayatul Muta'allimin Wonoayu Sidoarjo - Ikwandi, Muhamad Ripin; Aminullah, Rivky Musyaddad; Puspitaningtyas, Eny (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
ABSTRAK Madrasah MTs Hidayatul Muta'allimin Wonoayu Sidoarjo is a Tsanawiyah Madrasah with two superior programs, namely the Entrepreneurship Program and Tahfidzul Quran. The Role and Methods of MTt Hidayatul Muta'allim Wonoayu Sidoarjo in Incorporating an Entrepreneurial Vision So that Students Understand the Importance of Entrepreneurship Knowledge. This research is qualitative research conducted at MTs Hidayatul Muta'allim Wonoayu Sidoarjo. Data was collected through observation, interviews and documentation. The findings of this research are the role of MTt Hidayatul Muta'allim Wonoayu Sidoarjo in building entrepreneurial skills and their application in the proposed program. Making Instant Ginger products is always taught so that you can make a tutorial on making Instant Ginger MTs Hidayatul Mutaallimin. Apart from that, students will also receive product marketing training via WA status, online stores via Instagram. , Facebook. With the help of entrepreneurship, students are expected to gain knowledge and skills and develop entrepreneurial traits and personalities. Entrepreneurship development trains students to be independent and self-confident as well as a sense of responsibility and independence